Fixing American Politics : solutions for the media age - Hart, Roderick P.; Hart, Roderick P. (New York: Routledge, 2022)
"Fixing American Politics: Solutions for the Media Age contains the work of 34 scholars from two disciplines - Communication and Political Science - asked to identify the most pressing problem facing the American people and how it can be solved. Each author addresses the question quickly (in around 3,000 words) and directly, with the favored solution featured in their chapter title. The book gives the reader much to think about and much to argue about. Should news outlets be funded with public money rather than by private enterprise? Are the new social media a boon or a bane to political elections? Is the American past dead or is it living once again? Do churchgoers and environmentalists have anything to discuss? Is the F.C.C. doing its job? Can political ads be made less toxic? Should Fox News be "canceled"? Should cancel cultures be cancelled? Can we become more civil to one another and, if so, how? Fixing American Politics has all the best questions ... and some answers as well"--
Includes bibliographical references and index.
Introduction. Chapter 1: "Make Politics Your Passion" -- Unit 1. Make History Functional. Chapter 2: "Let's Find a Usable Past" -- Chapter 3: "Understand Your Moment in Time" -- Chapter 4: "Heed the Prophetic Voice" -- Chapter 5: "Experiment with Playful Protest" -- Unit 2. Exploit Human Capacities. Chapter 6: "Let Consensus Overcome Polarization" -- Chapter 7: "Use Emotion Wisely" -- Chapter 8: "Explore the Reasons for Incivility" -- Chapter 9: "Tell the Story of Poverty" -- Chapter 10: "Imagine New Political Coalitions" -- Unit 3. Open Your Mind. Chapter 11: "Listen to the First Amendment" -- Chapter 12: "Hear the Presidency Differently" -- Chapter 13: "Fix the 'Cancel Culture' Mentality" -- Chapter 14: "Cultivate Empathy for Outgroups" -- Unit 4. Confront the Establishment. Chapter 15: "Counter a Reactive Media System" -- Chapter 16: "Create a Watchdog Branch of Government" -- Chapter 17: "Modernize Healthcare Decision-making" -- Chapter 18: "Give Election Apps More Integrity" -- Chapter 19: "Shake-Up the F.C.C." -- Unit 5. Upgrade Political Campaigns. Chapter 20: "Study the Electorate Thoroughly" -- Chapter 21: "Talk About Voters Thoughtfully" -- Chapter 22: "Vote When Voting Really Counts" -- Chapter 23: "Make Ads Safe for Democracy" -- Chapter 24: "Let's Outperform Super PACs" -- Unit 6. Reimagine Traditional Journalism. Chapter 25: "Address Journalism's Crisis Boldly" -- Chapter 26: "Measure Newsroom Effectiveness Differently" -- Chapter 27: "Publicly Subsidize Journalism" -- Chapter 28: "Report on Terrorism Responsibly" -- Chapter 29: "Challenge Fox News" -- Conclusion. Chapter 30: "Enliven Your Civic Capacities."
Keywords: Politics, Practical -- United States; Mass media and public opinion -- United States; United States -- Politics and government -- 21st century